Multi-fractured stimulation technique of hydraulic fracturing assisted by the DTH-hammer-induced impact fractures. (November 2019) - Li, Yanliang; Peng, Jianming; Huang, Chaoyang; Lian, Moke; Xu, Tianfu; Zhang, Yanjun; Bo, Kun; Feng, Bo; Zhou, Jian
Highlights: A novel technique of hydraulic fracturing assisted by the DTH-hammer-induced impact fractures is proposed. Complex fracture networks can be formed near the wellbore. The novel technique can significantly reduce the fracturing pressure and improve the permeability near the wellbore. Abstract: Hydraulic fracturing is one of the key technologies in geothermal development of hot-dry-rock (HDR) geothermal energy. How to reduce the fracturing pressure and enhance the fractures connectivity of HDR has become a hot issue. In this paper, we propose to use a down-the-hole (DTH) hammer to impact granite, which assist to create new artificial fractures similar to natural fractures or widen the existing fractures near the wellbore, consequently enhancing the connectivity of fractures during hydraulic fracturing. A series of experiments were conducted to verify the feasibility of this stimulation technique, including the observation and quantification of impact fractures, and the determination of fracturing pressure. In addition, numerical simulation of impact stress wave was carried out to explain the distribution of fractures. The results showed that the granite rock mass damage caused by percussive rotary drilling was about 5–7 times larger than that caused by diamond rotary drilling. Meanwhile, the distribution of fractures was characterized by regionalization, which was mainly attributed to the attenuation of impact stress wave, and the numerical results were consistent with the experimental observations. Laboratory experiment results of hydraulic fracturing indicated that the fracturing pressure of granite samples near the wellbore after percussive drilling had been greatly reduced, which was nearly 50% lower than that of conventional drilling. It indicates that the proposed multi-fractured stimulation technique of hydraulic fracturing assisted by the impact fractures induced by a DTH hammer can be a potential solution to solve the problems of hydraulic fracturing.